USING STORY GRAMMAR STRATEGY TO IMPROVE READING COMPREHENSION - Nuril Indriana (Universitas Islam Ogan Komering Ilir Kayuagung, 2018)
Reading is a necessary skill that required by students because reading is a vital skill to get information. Story grammar strategy can be used to improve students’ comprehension in understanding the text. The objective of the study was to find out whether or not there was a significant difference in reading comprehension between the students who were taught by using story grammar strategy and that of those who were not. The method used in this study was a quasi-experimental method. The sample of this study was 60 students which divided into two groups, namely experimental group (class XI IPA 2) and control group (class XI IPA 3). To collect the data, the written test in the form of multiple choices was administered. The t-test was to analyze the data. The result of t-test was 13.7 the significance level of p<0.05 with df 58, the critical value of t-table was 1.9944 so that 13.7>1.9944, it showed that the null hypothesis (Ho) was rejected and the research hypothesis (Ha) was accepted. It meant that there was a significant difference in reading comprehension between students who were taught by using story grammar strategy that of those who were not. In conclusion, story grammar can be used to improve students’ reading comprehension